2022
DOI: 10.1111/cpr.13229
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Rab11‐mediated endocytic trafficking of LDL receptor contributes to angiotensin II‐induced cholesterol accumulation and injury in podocytes

Abstract: Objectives: Exposure of podocytes to angiotensin II (Ang II) enhances the abundance of the cell surface glycoprotein, low-density lipoprotein receptor (LDLR) and promotes significant changes in the cellular cholesterol content. Recent investigation provides evidence that the small GTPase Rab11 is involved in the regulation of LDLR, but the exact mechanisms remain unknown. In this study, the role of Rab11 in posttranscriptional regulation of LDLR was evaluated to investigate potential mechanisms of podocyte cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Conditionally immortalized human podocytes (HPCs) cell line was obtained from Dr. Moin A. Saleem (Academic Renal Unit, Southmead Hospital, Bristol, UK). HPCs were grown as described previously 16 . Briefly, HPCs were cultured in RPMI‐1640 basal medium (glucose 5.5 mM, HyClone, USA) containing 10% heat‐inactivated fetal bovine serum (FBS; Gibco, USA), penicillin G (100 IU/mL), streptomycin (100 mg/mL) and 1× insulin‐transferrin‐selenium (ITS; Invitrogen, USA) at 33°C for proliferation; then they were thermoswitched to 37°C for 10–14 days without ITS to induce differentiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditionally immortalized human podocytes (HPCs) cell line was obtained from Dr. Moin A. Saleem (Academic Renal Unit, Southmead Hospital, Bristol, UK). HPCs were grown as described previously 16 . Briefly, HPCs were cultured in RPMI‐1640 basal medium (glucose 5.5 mM, HyClone, USA) containing 10% heat‐inactivated fetal bovine serum (FBS; Gibco, USA), penicillin G (100 IU/mL), streptomycin (100 mg/mL) and 1× insulin‐transferrin‐selenium (ITS; Invitrogen, USA) at 33°C for proliferation; then they were thermoswitched to 37°C for 10–14 days without ITS to induce differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…HPCs were grown as described previously. 16 Briefly, HPCs were cultured in RPMI-1640 basal medium (glucose 5.5 mM, HyClone, USA) containing 10% heat-inactivated fetal bovine serum (FBS; Gibco, USA), penicillin G (100 IU/mL), streptomycin (100 mg/mL) and 1Â insulin-transferrin-selenium (ITS; Invitrogen, USA) at 33 C for proliferation; then they were thermoswitched to 37 C for 10-14 days without ITS to induce differentiation. All experiments were performed with differentiated cells.…”
Section: Cell Cultures and Treatmentsmentioning
confidence: 99%
“…High cholesterol levels are considered as a risk factor for atherosclerosis but are also closely related to other diseases, such as chronic kidney disease, osteoporosis, diabetes mellitus and lung diseases. [23][24][25][26] Recent studies have demonstrated that cholesterol plays an important role in pulmonary diseases. 17 In lung cancer, cancer tissues contain more free cholesterol and cholesterol ester than para-cancer tissues.…”
Section: Cholesterol Metabolism and Its Role In Copdmentioning
confidence: 99%
“…Different processes of cholesterol metabolism are regulated by different factors in diseases. High cholesterol levels are considered as a risk factor for atherosclerosis but are also closely related to other diseases, such as chronic kidney disease, osteoporosis, diabetes mellitus and lung diseases 23–26 . Recent studies have demonstrated that cholesterol plays an important role in pulmonary diseases 17 .…”
Section: Cholesterol Metabolism and Its Role In Copdmentioning
confidence: 99%